2023
DOI: 10.35241/emeraldopenres.14904.1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of perception of climate change and adaptation strategies of coffee-based agroforestry farmers in western Ethiopia

Abstract: Background: A range of local social and environmental factors has an impact on farmers' views of climate change and choices on the use of coping mechanisms. This study examines the factors that are limiting farmers' perceptions of climate change and their coping mechanisms in Gimbi district, Western Ethiopia. Methods: A household survey and focus group discussion were employed to collect relevant data. A total of 402 randomly selected households and six focus group discussions containing 72 participants were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
(7 reference statements)
0
0
1
Order By: Relevance
“…The results also indicated that supplementary feeding for livestock (56%) was the most implemented adaptation response followed by soil and water conservation practices (19%), whereas crop diversification (2.1%) was the least common adaptation response to the adverse impacts of climate extremes by farmers in lowland agro-ecology. This result contradicts with the finding of [ 30 ] who reported that the possibility of using crop diversification was very high in lowland areas. Key informants and focus group discussants also reported that soil and water conservation practices and feeding for livestock were the most widely used adaptation measures in highland and lowland areas of the district.…”
Section: Resultscontrasting
confidence: 99%
“…The results also indicated that supplementary feeding for livestock (56%) was the most implemented adaptation response followed by soil and water conservation practices (19%), whereas crop diversification (2.1%) was the least common adaptation response to the adverse impacts of climate extremes by farmers in lowland agro-ecology. This result contradicts with the finding of [ 30 ] who reported that the possibility of using crop diversification was very high in lowland areas. Key informants and focus group discussants also reported that soil and water conservation practices and feeding for livestock were the most widely used adaptation measures in highland and lowland areas of the district.…”
Section: Resultscontrasting
confidence: 99%